PENGEMBANGAN MEDIA PEMBELAJARAN LUMI EDUCATION BERBASIS H5P PADA MATERI SISTEM PENCERNAAN - Juni Harja, Endra; M. Nasir (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop interactive learning media using the Lumi Education platform based on H5P for eighth-grade students of SMP/MTs (Junior High School), in response to the limitations of conventional approaches that lack dynamic visualization. The method employed in this study is Research and Development (R&D) using the ADDIE model, which encompasses five stages: Analysis, Design, Development, Implementation, and Evaluation. The developed media integrates Discovery Learning syntax through multimedia elements such as interactive videos, images, and formative evaluations, thereby promoting active student engagement throughout the learning process. Media validity was assessed by three expert validators two multimedia specialists and one science teacher using Aiken's V formula applied to 38 instrument items covering four aspects: design, pedagogy, content, and technical quality. The validation results yielded an overall index of 0.805, which falls within the high validity category. The pedagogical aspect received the highest score, with several indicators reaching a value of V = 0.917, reflecting that the learning media has met the required educational standards and is highly appropriate for use in supporting classroom instructional activities. The design aspect also excelled in terms of color composition and the function of supporting images (V = 0.917). Overall, the H5P-based Lumi Education learning media is declared valid and suitable for implementation in science learning at the SMP/MTs level, with recommendations for improvement in navigation flexibility and assessment instruments. Keywords: Lumi Education, H5P, interactive learning media, digestive system, ADDIE model